Communication, technology and cultural change - Krug, Gary (SAGE, 2005)
Written accessibly, and tightly edited, with each chapter following the same conceptual structure. This volume takes a fresh approach in its analysis of the future of the welfare state in Europe. It suggests that opportunities for radical change in welfare systems are now opening up, and that there will be little continuity between the future and the past/present of the welfare system in Europe.